New evidences on the regulation of SF-1 expression by POD1/TCF21 in adrenocortical tumor cells - França, Monica Malheiros (2017)
OBJECTIVES: Transcription Factor 21 represses steroidogenic factor 1, a nuclear receptor required for gonadal development, sex determination and the regulation of adrenogonadal steroidogenesis. The aim of this study was to investigate whether silencing or overexpression of the gene Transcription Factor 21 could modulate the gene and protein expression of steroidogenic factor 1 in adrenocortical tumors. METHODS: We analyzed the gene expression of steroidogenic factor 1 using qPCR after silencing endogenous Transcription Factor 21 in pediatric adrenal adenoma-T7 cells through small interfering RNA. In addition, using overexpression of Transcription Factor 21 in human adrenocortical carcinoma cells, we analyzed the protein expression of steroidogenic factor 1 using Western blotting. RESULTS: Transcription Factor 21 knockdown increased the mRNA expression of steroidogenic factor 1 by 5.97-fold in pediatric adrenal adenoma-T7 cells. Additionally, Transcription Factor 21 overexpression inhibited the protein expression of steroidogenic factor 1 by 0.41-fold and 0.64-fold in two different adult adrenocortical carcinoma cell cultures, H295R and T36, respectively. CONCLUSIONS: Transcription Factor 21 is downregulated in adrenocortical carcinoma cells. Taken together, these findings support the hypothesis that Transcription Factor 21 is a regulator of steroidogenic factor 1 and is a tumor suppressor gene in pediatric and adult adrenocortical tumors.